Analyzing Influential Factors Against Timeliness of Financial Reporting (Empirical Study of Automation and Components and Telecommunication Companies Listed on Indonesia Stock Exchange). - Joko Suryanto; Indra Pahala (Fakultas Ekonomi, Universitas Negeri Jakarta, 2016)
This research aims to examine the effect of the relationship between firm size, profitability, solvency, public ownership, and the audit opinion on the timeliness of financial reporting. The dependent variable in the form of timekeeping company deliver the financial statements to the Stock Exchange. Meanwhile for the independent variables such as firm size measured by total asets of the company, profitability is measured by profit margin ratio, solvency measured by debt-to-equity ratio, public ownership is measured by the percentage of the number of shares owned by the community, and the audit opinion is measured with an unqualified opinion and otherwise unqualified. This study uses secondary data with population automotive companies and telecommunications components and annual financial statements issued on the Stock Exchange in the period 2010-2012. From the analysis conducted in this study it can be concluded that the size of the company significantly influence the timeliness of financial reporting. While profitability, solvency, public ownership, and the audit opinion does not affect the timeliness of financial reporting. Keywords: Company Size, Profitability, Solvency, Public Shareholding, Opinion Audit and Financial Reporting Timeliness.